Congenital hypogonadotropic hypogonadism, functional hypogonadotropism or constitutional delay of growth and puberty? An analysis of a large patient series from a single tertiary center. Issue 1 (16th December 2016) - Varimo, Tero; Miettinen, Päivi J.; Känsäkoski, Johanna; Raivio, Taneli; Hero, Matti
Abstract : STUDY QUESTION: What diagnoses underlie delayed puberty (DP) and predict its outcome? SUMMARY ANSWER: A multitude of different diagnoses underlie DP, and in boys a history of cryptorchidism, small testicular size and slow growth velocity (GV) predict its clinical course. WHAT IS KNOWN ALREADY: DP is caused by a variety of underlying etiologies. Hormonal markers can be used in the differential diagnosis of DP but none of them have shown complete diagnostic accuracy. STUDY DESIGN, SIZE, DURATION: Medical records of 589 patients evaluated for DP in a single tertiary care center between 2004 and 2014 were retrospectively reviewed. PARTICIPANTS/MATERIALS, SETTING, METHODS: Clinical and biochemical data of 174 boys and 70 girls who fulfilled the criteria of DP were included in the analyses. We characterized the frequencies of underlying conditions and evaluated the predictive efficacy of selected clinical and hormonal markers. MAIN RESULTS AND THE ROLE OF CHANCE: Thirty etiologies that underlie DP were identified. No markers of clinical value could be identified in the girls, whereas a history of cryptorchidism in the boys was associated with an increase in the risk of permanent hypogonadism (odds ratio 17.2 (95% CI; 3.4-85.4, P < 0.001)). The conditions that cause functional hypogonadotropic hypogonadism were more frequent in boys with a GV below 3 cm/yr than in those growing faster (19% vs 4%, P < 0.05). In this series, the most effective markers to discriminate the prepubertal boys with constitutional delay of growth and puberty (CDGP) from those with congenital hypogonadotropic hypogonadism (CHH) were testicular volume (cut-off 1.1 ml with a sensitivity of 100% and a specificity of 91%), GnRH-induced maximal LH (cut-off 4.3 IU/L; 100%, 75%) and basal inhibin B (INHB) level (cut-off 61 ng/L; 90%, 83%). LIMITATIONS, REASONS FOR CAUTION: The main limitation of the study is the retrospective design. WIDER IMPLICATIONS OF THE FINDINGS: Prior cryptorchidism and slow GV are two important clinical cues that may help clinicians to predict the clinical course of DP in boys, whereas markers of similar value could not be identified in girls. In prepubertal boys, testicular size appeared as effective as INHB and GnRH-induced LH levels in the differential diagnosis between CHH and CDGP. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Academy of Finland (268356), Foundation for Pediatric Research (7495), Sigrid Juselius Foundation (2613) and the Finnish Medical Foundation (011115). The authors have no competing interests to report. TRIAL REGISTRATION NUMBER: Not applicable.